The doripenem serum concentrations in intensive care patients suffering from acute kidney injury, sepsis, and multi organ dysfunction syndrome undergoing continuous renal replacement therapy slow low-efficiency dialysis - Wieczorek A; Tokarz A; Gaszynski W; Gaszynski T (Dove Medical Press, 2014)
Andrzej Wieczorek, Andrzej Tokarz, Wojciech Gaszynski, Tomasz Gaszynski Department of Anesthesiology and Intensive Therapy, Medical University of Lodz, Lodz, Poland Abstract: Doripenem is a novel wide-spectrum antibiotic, and a derivate of carbapenems. It is an ideal antibiotic for treatment of serious nosocomial infections and severe sepsis for its exceptionally high efficiency and broad antibacterial spectrum of action. Doripenem is eliminated mainly by the kidneys. In cases of acute kidney injury, dosing of doripenem depends on creatinine clearance and requires adjustments. Doripenem is eliminated during hemodialysis because its molecular weight is 300–400 Da. The aim of this study was to establish the impact of continuous renal replacement therapy (CRRT) slow low-efficiency dialysis (SLED) on doripenem serum concentrations in a population of intensive-therapy patients with life-threatening infections and severe sepsis. Ten patients were enrolled in this observational study. Twelve blood samples were collected during the first administration of doripenem in a 1-hour continuous infusion while CRRT SLED was provided. Fluid chromatography was used for measurement of the concentration of doripenem in serum. In all collected samples, concentration of doripenem was above the minimum inhibition concentration of this antibiotic. Based on these results, we can draw the conclusion that doripenem concentration is above the minimum inhibition concentration throughout all of CRRT. The dosing pattern proposed by the manufacturer can be used in patients receiving CRRT SLED without necessary modifications. Keywords: AKI, antibiotic, antimicrobial therapy, carbapenem, CRRT, infection, MODS, SLED